Application of project management using the critical path method (CPM) in residential construction projects - Satryawati, Satryawati; Zunaidah, Umi; Qumairo, Eny Lathifa; Nurhalizah, Selviana; Tambing, Wyenda (Enrichment : Journal of Management, 2025)
This study aims to analyze the application of the CPM in residential construction project in Samarinda City, in order to optimize the efficiency of implementation time. The approach used was descriptive quantitative, with data collection through field studies, documentation, and interviews. The CPM was applied by identifying all project activities, compiling a work network diagram, backward pass, and determining the earliest and latest possible start and finish times. The results showed that the project critical path had a total duration of 77 days. Delays in any of the activities on this path will have a direct impact on the overall project delay. Conversely, activities outside the critical path have time slack. These findings show that the CPM method is effective in assisting systematic and data-driven project planning and control, and makes a real contribution to improving time efficiency in the residential construction sector